2013
DOI: 10.1093/gerona/glt070
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Density, a Novel Biomarker Predicting Mortality Risk in Older Adults

Abstract: VAT and SAT density provide a unique marker of mortality risk that does not appear to be inflammation related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
131
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(148 citation statements)
references
References 29 publications
16
131
1
Order By: Relevance
“…More recently, Fox et al 12 examined associations between SAT and VAT attenuation values and cardiometabolic risk factors. They found that low CT attenuation of both VAT and SAT 13 was associated with an adverse cardiometabolic risk profile, independent of total adiposity. In 2014, Murphy et al 13 have shown that SAT and VAT attenuation values were good markers of mortality risk in older adults, independent of CRP and IL-6 levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Fox et al 12 examined associations between SAT and VAT attenuation values and cardiometabolic risk factors. They found that low CT attenuation of both VAT and SAT 13 was associated with an adverse cardiometabolic risk profile, independent of total adiposity. In 2014, Murphy et al 13 have shown that SAT and VAT attenuation values were good markers of mortality risk in older adults, independent of CRP and IL-6 levels.…”
Section: Introductionmentioning
confidence: 99%
“…They found that low CT attenuation of both VAT and SAT 13 was associated with an adverse cardiometabolic risk profile, independent of total adiposity. In 2014, Murphy et al 13 have shown that SAT and VAT attenuation values were good markers of mortality risk in older adults, independent of CRP and IL-6 levels. However, the reason for the relationship between adipose tissue attenuation and cardiometabolic risk is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, computed tomography-determined adipose-tissue density in the visceral and subcutaneous depots, which correlates with smaller adipocyte size and higher adiponectin concentrations, was shown to be an independent predictor of mortality in two older cohorts (26). Whether the positive association of adiponectin with mortality is independent of adipose-tissue density has not been reported, but would address the role of changes in adipocyte size and function as an underpinning in aging, and perhaps other disorders such as HF.…”
mentioning
confidence: 99%
“…A very recent study showed that lower density tissue determined from computed tomography imaging, an indication of greater fat content, was associated with less mortality (9). Another hypothesis is that BMI is a poor proxy for excess body fat and does not capture nuances of fat storage (10).…”
mentioning
confidence: 99%